-4x-6=2x-12

Simple and best practice solution for -4x-6=2x-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x-6=2x-12 equation:



-4x-6=2x-12
We move all terms to the left:
-4x-6-(2x-12)=0
We get rid of parentheses
-4x-2x+12-6=0
We add all the numbers together, and all the variables
-6x+6=0
We move all terms containing x to the left, all other terms to the right
-6x=-6
x=-6/-6
x=1

See similar equations:

| -3x+4=x+3 | | -3(2x-9)=-11 | | 15q+10=10q | | 7-14x+2=-2(x+4)-12x | | (X)+(5x+18)=90 | | 3(4p-1)=-6(4-p) | | 2x+1+6x-1=80 | | -7x+16=8 | | (9√3/3)^x=3^(x+1) | | -3b+2.6=4 | | |2x-6|+5=11 | | -2(m-18)=0 | | (25+65)x=(400+25)x | | 69=y-11 | | 2(3x-4)-10=-23 | | -2x+4x2=0 | | 16-18d=-19-20d-5 | | 1/25=3.8/x | | 27=4(1-x)+3(x+1) | | 3=u/5-7 | | 8+3xx=6 | | 64+36+4b=180 | | 5(4x+85)=3(x+51) | | 5(x-4)=3(2x-5 | | 4(w–9)=–48 | | -7x-180=-15x+100 | | 2(3x-4)-10=-23* | | -6(6p-2)-3p=-300 | | 0.25x=137.50 | | 6−2x+11=−5 | | 2x-9-3x=-11-x+2 | | 12+12x=3x+84 |

Equations solver categories